Implementasi Program Bina Lingkungan Sebagai Strategi Pengelolaan Tunggung Jawab Sosial Perusahaan: Tinajuan Dari Perspektif CSR - Armansyah (Program Studi Hukum Universitas Nusa Putra, 2023)
Corporations as business entities have obligations to social and environmental responsibility known as CSR. The community development program is the development of Corporate Social Responsibility (CSR) Implementation which is used as the Company's effort in sustainable development based on the 3P principle; namely Profit, People, and Planet. This study aims to analyze the implementation of the Community Development Program as a strategy in CSR management and analyze the implementation of CSR arrangements in the strategy of managing corporate responsibility in environmental aspects. The method in this study is normative juridical research. with the approach used, namely the Statutory Approach, Conceptual Approach, and Case Approach. The implementation of the Community Development program is a strategic step that can have a long-term positive impact on the company. One important aspect of the Community Development Program is its focus on sustainable development. Companies that involve themselves in this activity not only pay attention to the current environmental aspects but also aim to leave a positive for future generations. By adopting eco-friendly practices and sustainability projects, companies can create a sustainable positive impact in the long run. the implementation of Corporate Social Responsibility (CSR) arrangements in environmental responsibility management is an important step taken by companies to maintain a balance between business sustainability and social and environmental impacts. CSR regulation in environmental responsibility management is not just about complying with regulations or meeting market expectations. but also, as an effort to create long-term value, build strong relationships with stakeholders, and become agents of positive change in society.